The Effect of Storage on The Nutritional Quality of Pindang Broiler Chicken Meat Packed with a Plastic Vacuum Bag (Vacuum Pack) - Anita Mustika Ibrahim; Asis Surajat (Chalaza Journal of Animal Husbandry, 2021)
The body needs animal protein needs in this new normal. This research aimed to determine the storage time for Pindang seasoned broiler chicken, which was packaged using a plastic vacuum bag (vacuum pack). The problem with this research was that the exact length of storage for Pindang Spice broiler chicken's nutritional quality wasn’t known by using a vacuum pack. This research will be conducted for one year (12 months). This research will be conducted in Bau-Bau City, Betoambari road, Bones village. Analysis of the nutritional content of Pindang Spiced broiler chickens meat will be carried out at the UHO Faculty of Animal Husbandry Technology Laboratory. The research that will be conducted is experimental. The research used a Completely Randomized Design with four treatments and four replications, each consisting of 500 grams of pindang seasoned broiler chickens. The research data were analyzed using analysis of variance (ANOVA) based on a completely randomized design using the SPSS standard. Further testing was carried out with the Duncan Multiple Range Test if the treatment had a significant effect. Based on the results of this research, it can be concluded that the protein content and fat content significantly (P0.05) on the nutritional quality of Pindang Spiced Broiler chicken meat packaged in a vacuum pack. At the same time, the best treatment was obtained on the length of use of the vacuum pack on the nutritional quality of the results of this research, namely in the P2 treatment (10 days of storage), where the protein content, fat content, and water content of the meat were of higher quality.